Socio-demographic and governance drivers of sanitation participation: Preliminary Evidence from Gorontalo City, Indonesia - Evi Siti Sofiyah; I Wayan Koko Suryawan; Ari Rahman; Nova Ulhasanah; Mega Mutiara Sari (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
This study examines household willingness to participate in community-based sanitation governance in Gorontalo Province, Indonesia, where marine natural capital is increasingly threatened by inadequate sanitation. A cross sectional survey of 63 households was conducted using a structured questionnaire that measured governance performance, agency and empowerment, access, flexibility, and learning capacity. Exploratory factor analysis identified five latent dimensions, and subsequent cluster and logistic regression analyses tested the influence of socio-demographic and governance variables on willingness to participate. The hypothesis testing confirmed that socio-demographic characteristics (H1 gender, H2 age, H3 education, H4 occupation, H5 household expenditure, H6 household income) played limited roles, with only occupation and expenditure showing partial influence. In contrast, governance-related dimensions were decisive. Organizational performance (H7) and agency and governance (H8) did not reach significance in the binary model, but sanitation access (H9) strongly predicted willingness (p < 0.01), with flexibility also marginally significant. These results demonstrate that while socio-economic background shapes vulnerability, participation is primarily driven by equitable access and adaptive governance capacity. The findings underscore the urgent need for Gorontalo’s sanitation policies to integrate governance strengthening with marine ecosystem protection, ensuring that community participation contributes directly to safeguarding marine natural capital.